Microbiological Contamination Of Kerabu Dishes Sold At Cafes And Food Stalls In Universiti Sains Malaysia - ‘Asri, Norsyahira (Universiti Sains Malaysia, 2020)
“Kerabu” is a salad dish that is made up of multiple ingredients before they are mixed together without having any heat treatment for cooking. With the ingredients consisting of mostly fruits and vegetables, this dish is usually prepared fresh before being consumed. Having no cooking treatment, making this salad has a limited shelf life and due this factor, the safety of this dish can be questioned as there is no process used to reduce the microbial load of the dish. This study was conducted purposely to investigate the prevalence of microorganisms that are possible to be present in (ready-to-eat) RTE “kerabu” in cafes and food stalls in Universiti Sains Malaysia (USM), Penang. Twenty “kerabu” samples were collected and been analyzed for various analyzes which were total plate counts (TPC), yeast and mold count, total and fecal coliform and detection of Escherichia coli, Salmonella spp. and Staphylococcus aureus. Results showed that for TPC of the most of the samples were more than 107 CFU/g with the highest values was from sample 6 (kerabu taugeh) with 4.68x108 CFU/g, while yeast and mold with detection count also were more than 107 CFU/g with 1.78x108 CFU/g from sample 2 (kerabu taugeh). Five samples were recorded to have the highest values of CFU/g which is more than 1100 MPN/g for the fecal coliform and 2 samples were positive for Escherichia coli which were sample 1 (“kerabu mangga”) and sample 3 (“kerabu taugeh”). One sample was confirmed to be contaminated by Salmonella which was sample 4 (“kerabu mangga”). From the results, it can be concluded that RTE “kerabu” can serve as a vehicle for foodborne contamination, thus precautions should be taken to avoid food outbreak.